Acne and Its Variants in Special Populations. (January 2018) - St. Claire, Kayla; Lake, Eden P.
Abstract : ABSTRACT: Acne vulgaris is one of the most common medical conditions encountered in dermatology and primary care settings, affecting up to 50 million Americans annually. It is a disease of the pilosebaceous unit characterized by microcomedones, papules, pustules, and nodules that primarily affect the face, upper chest, and back. Although acne is commonly considered an oily disease of puberty, it is important to recognize that acne has various presentations, sequelae, and effects on quality of life in different populations. African Americans are more prone to scarring, hyperpigmentation, and keloid formation. Adult women may present clinically with dry skin and have more severe acne flares across the menstrual cycle with a greater psychological impact. Acne presenting in childhood should raise suspicion for various endocrinopathies if other clinical signs of androgen excess are present such as accelerated height velocity, enlarged genitalia, or pubic hair and are concurrent with advanced bone age. It is important for medical practitioners to familiarize themselves with these differing presentations and sequelae in specific populations to provide adequate evaluations and treatment regimens.